Pengaruh Project Based Learning Terhadap Hasil Belajar Metode Penelitian Akuntansi - Anggono Anggono; Keumala Hayati; Siti Dini; Munawarah Munawarah (Owner : Riset dan Jurnal Akuntansi, 2022)
The problem in this research is low learning outcome of students who studied research method. The purpose of this research was to examine the effect of project based learning on learning outcomes of accounting research method. The research population consisted of 39 students. The sampling technique in this research is simple random sampling, so the research sample is 36 students. The data collection technique used in this research was test. The data analysis technique was paired sample t test. The results of the research proved that project based learning has a positive and significant effect on the learning outcomes of accounting research method, in other words, the higher the implementation of project based learning, the higher the learning outcomes of accounting research methods. In conclusion, project based learning can be used in learning accounting.